Sport Entrepreneurial Mindset: A Narrative Study in Sport Products Entrepreneur Cluster - Chankuna, Dittachai; Ownsungnoen, Apiwan; Numboonjit, Alonggon (Journal of Industrial Business Administration, 2024)
The sports industry was affected by the COVID-19 pandemic, Shift to digital transformation. The future of growing to sport entrepreneur is unpredictable as the past. This qualitative research has the objective to synthesize the sport entrepreneurial mindset of sport product entrepreneur cluster. Interpretivism of Grounded Theory was employed as a research paradigm. Thirteen successful sport product entrepreneurs were purposive enrolled to be key informants. Data were collected from self-narrative inquiry followed by concluded the data with inductive approach. The results found that the sport entrepreneurial mindset was initiated from perceiving opportunity of success. Successful sport product entrepreneurs have a business-oriented vision, powerful inspiration, understand consumer’s needs, build business alliance, and utilize technology. University students, young generation, lecturers in educational institutes, and personnel in related-sport entrepreneur organizations are benefits when applying the results. The sport industry attains research values, to incubate the sport entrepreneurial and scale-up to innovation-driven enterprise.